Comparison of Physical and Mechanical Properties of Antifouling PVDF Membranes by Titanium Dioxide and PES Membrane by Titanium Dioxide. Issue 1 (January 2021) - Mataram, A; Nukman,; Nasution, J D; Riadi, M I; Pataras, M; Aditya, B B; Septano, G D; Anisya, N; Nadiyah, N A
Abstract: The main factor to support daily life is water, but the fact is there are approximately 2.1 billion people currently threatened with a shortage of clean water. Polyethersulfone (PES) and Polyvinylidene Fluoride (PVDF) are polymers that are commonly used for membrane fabrication because they have extraordinary properties in the screening process. The addition of addictive substances into the membrane formation process is no less important as supporting the ability to be even better in membranes Titanium Dioxide (TiO2) as an additive with properties relevant to the two polymers which can cover the shortcomings of the two polymers. The printing process of PVDF and PES membranes with the addition of TiO2 uses a copper plate which is flowed with an electric field of 15000V DC. The results of the surface morphology of Scanning Electron Microscopy (SEM) both showed extraordinary changes compared without modification to the printing process as in previous studies. The tensile strength test results showed uniformity with the membrane morphology and an increase in the maximum stress value of the membrane to 3.86 MPa. Surface roughness values can help identify membrane impurity properties which are also relevant to the results of water treatment performance tests and contact angles. Finally, the process of forming membranes with the additional modification of the printing process can open new avenues to maximize water treatment performance and service life on the membrane.